ADOLE (ADOPT A LEARNER) PROGRAM: A NETWORKING PROCESS IN IMPROVING THE ACEDMIC PERFORMANCE OF THE GRADE 11 STEM STUDENTS - Alvaro, Maria Elisa (IJBLE Scientific Publications Community Inc., 2022)
This qualitative-quantitative descriptive study sought to find out the effect of the intervention called AdoLe (Adopt-a- Learner) Program: A Networking Process. There were 18 out of 55 students who gained below 75%. The problems encountered by the students before intervention are low comprehension, working students, no form of communication, affected by Covid and lost outputs. The intervention consists of home visitation, one-on-one calls, one-on-one video calls, one-on- one audio clips, blended learning thru modular, online and radio- based information with the networking process of the different stakeholders. Based on the findings, there is a significant difference in the performance of the respondents before and after the intervention. the use of intervention has improved the performance level of grade 11 students in Personal Development.